Guaranteeing the independence of election management bodies in Africa : a study of the electoral commissions of Kenya and South Africa - Ampofo, K.K.K. (University of Pretoria, 2006)
Prepared under the supervision of Mr. Kingsley Kofi Kuntunkrunku Ampofo at the Faculty of Law, University of Ghana